2008
DOI: 10.1007/s11095-008-9699-8
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Local Anesthetic Action Through Slow Release from Poly(Lactic Acid Co Castor Oil)

Abstract: Previously we developed a ricinoleic acid based polymer with incorporated bupivacaine which prolonged anesthesia to 30 h. The new polymer poly(lactic acid co castor oil) 3:7 provides slow release of effective doses of the incorporated local anesthetic agent and prolongs anesthesia to 48 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…On the contrary, incorporation of bupivacaine into polymer carrier is easy and reliable and offers high loading potential. Previously, we demonstrated that poly(lactic acid co castor oil 3:7) loaded with 10% bupivacaine and 15% bupivacaine formulation prolonged in vivo efficacy of bupivacaine up to 48 (12) and 96 (13) hours, respectively. However, these formulations were viscous (about 10,000 cP) at room temperature, which hindered their injectability.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…On the contrary, incorporation of bupivacaine into polymer carrier is easy and reliable and offers high loading potential. Previously, we demonstrated that poly(lactic acid co castor oil 3:7) loaded with 10% bupivacaine and 15% bupivacaine formulation prolonged in vivo efficacy of bupivacaine up to 48 (12) and 96 (13) hours, respectively. However, these formulations were viscous (about 10,000 cP) at room temperature, which hindered their injectability.…”
Section: Introductionmentioning
confidence: 95%
“…Bupivacaine free base was prepared from bupivacaine hydrochloride by alkaline precipitation and filtration as previously described (12). Two additives: ricinoleic acid (RA) or castor oil (CO) were selected as potential liquefying agents, and their effect on previously reported polymerbupivacaine formulations was examined in vitro and in vivo.…”
Section: Preparation Of Formulation and In Vitro Drug Releasementioning
confidence: 99%
See 2 more Smart Citations
“…Previous data shows that single injection of bupivacaine in poly(d,l:lactic acid-co-castor oil) 3:7 caused sensory block in mice that lasted 48 hours. 17,18 In our previous study, the PELA copolymers were well developed and their released characterization was ~1 week in vitro. 19 However, little information is available about the Rop-loaded nanoparticle (Rop-PELA) and its effects for sciatic nerve block on postoperative pain in vivo.…”
Section: Introductionmentioning
confidence: 99%